The use of films in the teaching of English as a foreign language: a systematic literature review - Estefanía Sánchez-Auñón; Pedro Antonio Férez-Mora; Fuensanta Monroy-Hernández (Asian-Pacific Journal of Second and Foreign Language Education, 2023)
Abstract Background Especially over the last decades, the use of cinema in the English as a foreign language (EFL) class has been gaining momentum. Although this interest has resulted in a complex body of research, no review to date had aimed to systematically map out (i) the pedagogical guidelines available for English teachers to implement films in class; (ii) the perceptions of EFL teachers and learners on the educational use of films; and (iii) the impact of cinema-based EFL on students’ learning, pertinent aspects as they contribute to deactivate instructors’ reported reluctance to use films as a proper teaching material. Thus, a systematic literature review has been conducted along the three previously-mentioned research questions with the aim of highlighting in a comprehensive manner the robust pedagogical value of cinema in EFL contexts. Methods A systematic search was carried out in Web of Science, ERIC, MLA International Bibliography, Education Database, and Scopus, which were last consulted on 2 December, 2022. Inclusion and exclusion criteria were applied, which covered journal papers written in English, peer-reviewed, published in open-access, and focusing on the exploitation of films for the teaching of English as a foreign language. Following the search and selection stages, a coding scheme was established, and the authors conducted a thematically based qualitative analysis to answer the research questions. Reliability was tested to check the agreement rate among the researchers. Findings Of the 416 sources found, 44 were eligible. Twenty-five percent of the selected references consist of theoretical or practical methodological orientations for the implementation of films in the EFL class, 16% of the sources explore EFL teachers’ and students’ perceptions on the educational use of films, and the remaining 59% of the references tap into the impact of cinema-based EFL on students’ learning. The results revealed that more informed guidelines on the exploitation of this resource are needed, that both instructors and teachers have a great attitude towards this method, and that films provide EFL learners with linguistic, intercultural, and motivational benefits. Interpretation On a general note, scholars have adopted a narrow focus when exploring cinema-based English teaching since they only address some of its benefits and they have mostly concentrated on the University educational context. Specific research gaps are highlighted in relation to each research question, and avenues for further research are proposed. Finally, pedagogical implications for the educational use of cinema in the English class are provided.